Impact of Chromium on Morphological, Growth and Yield on Vigna ungiculata (L.) Walp. - unisha Begam1, S. James1, P.S. Sharavanan2*; M. Noor (Journal of Experimental Sciences, 2010)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Heavy metal contaminants in to the aquatic system has various sources, such as smelting processes and fuel combustions via atmospheric fall-outs, pollution from lakes, effluents and dumping activities. With these the run-off water system also takes the atmospheric inputs, sewage materials and leaching of carbages along with it. On the other hand, these polluted water bodies enter the terrestrial ecosystem in many path ways such as irrigation, degrading activities and biota flux. An attempt has been made to assess the response of cowpea cultivars under the effect of potassium di chromate with special reference to seed germination, seedling growth and yield. Various concentrations of potassium di chromate (Control, 10, 25, 50,100 and 250 mg kg-1 soil) were prepared and used for germination studies. The morphometrical parameters like root length, shoot length, number of leaves, number of root nodules and yield parameters were showed decreasing trend with the increasing of potassium di chromate concentrations. The minimum value was recorded at 250 mg kg-1 soil in the variety (Co-1). It is evident from the results obtained that the increase of potassium di chromate concentrations affected all growth parameters and also yield parameters. The concentration above 250 mg kg-1 soil was found to be completely lethal. — 1Department of Botany, Bharathiar University, Coimbatore; 2Department of Botany, Annamalai University, Annamalai Nagar